2017
DOI: 10.5694/mja17.00692
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mental health care attributes by diagnosis and clinical stage: the views of youth mental health clinicians

Abstract: A combination of clinical stage and disorder information might be an appropriate basis for ensuring that the right attributes of early intervention mental health care are provided to the right young people at the right time. Policy and research priorities include trialling novel services, preferences research among young people, strengthening service responses to subthreshold disorders and promoting high-fidelity collection of clinical stage data in youth mental health settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Thus, hYEPP clinicians may have greater opportunities for deeper knowledge of their clients, including being able to gauge neurocognitive function and observe potential impairments. A recent international survey of youth mental health practitioners found that neuropsychological assessment was believed to be relatively more important for psychosis than other disorders (Hamilton et al, ). Taken together, there is strong alignment between previous objective and the current subjective findings, indicating that the assessment and management of neurocognitive impairments is an essential component of early intervention for mental ill health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hYEPP clinicians may have greater opportunities for deeper knowledge of their clients, including being able to gauge neurocognitive function and observe potential impairments. A recent international survey of youth mental health practitioners found that neuropsychological assessment was believed to be relatively more important for psychosis than other disorders (Hamilton et al, ). Taken together, there is strong alignment between previous objective and the current subjective findings, indicating that the assessment and management of neurocognitive impairments is an essential component of early intervention for mental ill health.…”
Section: Discussionmentioning
confidence: 99%
“…Holistic and timely assessment has been identified as an important and potentially cost‐effective attribute of youth mental health services (Hamilton et al, ). Neurocognitive and symptom assessment specifically, is internationally recognised as important to youth mental health care (Hamilton et al, ). CNA is the most comprehensive and reliable means to assessing neurocognitive functioning in individuals (Braun et al, ; Lezak, Howieson, & Loring, ; Meyer et al, ; Roebuck‐Spencer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This highly personalised and measurement‐based model of care, linked to relevant service structures, has the potential to better match treatment type and intensity (defined by cost, time and risk). The clear goals are to prevent illness progression and promote recovery …”
Section: A Service Delivery Model To Support Highly Personalised and mentioning
confidence: 99%
“…Transitions within stepped or staged care processes may be required so that young people receive the level of care that best meets their needs (Hamilton et al, ). For example, headspace centres are expected to be strongly connected with local schools so that young people can be identified as in‐need at school and receive a well‐coordinated approach to care at the local headspace centre.…”
Section: Service Componentsmentioning
confidence: 99%